Trends and issues of electronic waste and mobile phone waste: A review of Malaysia context - Ismail, Mohd Azril; Lamsali, Hendrik; Lee, Choon Tong (2018)
For the past few decades, electrical and electronic equipment has transformed our daily activities dramatically.Although electrical and electronic equipment makes our life convenient, however, it will cause an environmental issue if it is not handled in appropriate disposal manner once those equipment reach end-of-life. Therefore, electronic waste and mobile phone waste has become a serious environmental issue in the 21st century. In this study, a review of the electronic waste and mobile phone waste in Malaysia will be conducted through the past academic literature and secondary data such as data from United Nation report, World Bank report, Department of Environment Malaysia report and Malaysian Communications and Multimedia Commission report. Meanwhile, the recommendation section will be provided based on the review finding.